Flow management of first-time orders: a dental office case study - Majewski A.; Merkisz-Guranowska A.; Czarnota K. (Журнал інженерних наук)
The article presents the importance of managing the flow of first-time patients in a dental practice. Three main areas of difference between the popular linear model of dental office operation on the market and the author’s model of an integrated multi-specialist dental team were analyzed. Performance indicators for working with first-time patients illustrating the ability to manage the flow of patients in the office, communicate with patients, build patient awareness of oral health conditions, and harness patients’ potential for treatment are presented and discussed. It was proven that with the fuller utilization of patients’ potential for treatment, a noticeable effect is a simultaneous increase in the profitability of the dental practice, which, with an entirely ethical process based solely on diagnosed dental problems, makes both profitable.